Research on psychoactive plants at Mexico’s National Medical Institute, 1888-1915 - Sarabia, Angélica Morales; Reynoso, Mariana Ortiz (Circumscribere International Journal for the History of Science, 2015)
The aim of the present essay is to analyze the work performed at the National Medical Institute (NMI) with a group of plants remarkable for containing significant psychoactive principles. The studies on the NMI conducted up to the present time did not analyze in depth the place those substances had in the Institute’s research agenda. For that reason we sought to identify the medicinal plants studied at NMI together with their active principles, the diseases to which they were experimentally applied, and the procedures used to study them. To illustrate that process we present two particular cases: peyote (Lophophora williamsii (Lem.) J.M. Coult) and white sapote (Casimiroa edulis La Llave & Lex.).